Global Mistrust in News: The Impact of Social Media on Trust. Issue 2 (2nd April 2020) - Park, Sora; Fisher, Caroline; Flew, Terry; Dulleck, Uwe
ABSTRACT: Digital platforms such as search engines and social media have become major gateways to news. Algorithms are used to deliver news that is consistent with consumers' preferences and individuals share news through their online social networks. This networked environment has resulted in growing uncertainty about online information which has had an impact on news industries globally. While it is well established that perceptions of trust in news found on social media or via search engines are lower than traditional news media, there has been less discussion about the impact of social media use on perceptions of trust in the news media more broadly. This study fills that gap by examining the influence of social media as news sources and pathways to news on perceptions of the level of news trust at a country level. A secondary data analysis of a 26-country survey in 2016 and 2019 was conducted. The analysis revealed an increase in social media use for accessing news resulted in a decline in trust in news media generally across the globe. Higher levels of general mistrust in news were related to an increased use of sharing of news. This paper argues the use of social media for news is closely linked to the increase in news mistrust, which is likely to continue to rise as the number of people using social media to access news continues to grow.